NOVÉL IMAH AGRÉNG KARYA AAM AMILIA (ULIKAN STRUKTURAL JEUNG ANTROPOLOGI SASTRA) - Fajar Purnama Sidik, - (2022)
The study deals with the structure of stories and the literary anthropology in the novel Imah Agreng by Aam Amilia. The purpose of this study is to describe (1) the theme, (2) the facts of the story, (3) the literary tools, and (4) the literary anthropological elements found in the novel Imah Agreng by Aam Amilia. The method used in this study is an analytical description along with a library study technique. The result of this littering is: (1) the themes discovered are murder mysteries and hypocrisy. (2) the story facts of this novel include plot, characters, and settings; The plot used is the mixed plot through ten episodes; The main character of the story Jaka and the additional one were found by ten; The setting in this novel is divided into three sections, namely, 6 place settings, 14 time settings, and 3 social backgrounds. (3) the literary tools of the novel include titles, point of view, and figures of speech; The title Imah Agreng describes a story centered on a luxurious home of Adiguna; Perspective employs the first-person method as the primary character; The figures of speech found in the novel Imah Agreng have four types: hyperbole, personification, metaphor, and similes. (4) the literary anthropology encompassed all the elements of the past, local wisdom, folklor (oral traditions and oral literature), and myth. The conclusion of the novel Imah Agreng by Aam Amilia has a complete story structure built on the elements of literary anthropology.